2020
DOI: 10.1186/s41182-020-00260-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of imported COVID-19 cases worldwide: early assessment of airport entry screening, 24 January until 17 February 2020

Abstract: The purpose of this study was to provide an overview of entry screening measures applied at airports in response to the COVID-19 epidemic worldwide. Between 24 January and 17 February 2020, 5.2% (95% CI 3.1–8.5) of the 271 total imported COVID-19 cases worldwide (excluding imported cases arriving in China, Macao, and Hong Kong) with known detection location were captured through airport entry screening. The majority of imported COVID-19 cases (210) were identified by the health care system (77.5%). Efforts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…found extremely low or no utility in differentiating infected from uninfected [119]. For COVID-19, similar findings have been reported, with only a very small proportion of SARS-CoV-2 infection cases detected during such screening practices [120]. Again, such measures divert resources and attention away from much more effective strategies to control infection.…”
Section: De-emphasize Excessive Surface Disinfection and Other Unnecessary Measuressupporting
confidence: 55%
“…found extremely low or no utility in differentiating infected from uninfected [119]. For COVID-19, similar findings have been reported, with only a very small proportion of SARS-CoV-2 infection cases detected during such screening practices [120]. Again, such measures divert resources and attention away from much more effective strategies to control infection.…”
Section: De-emphasize Excessive Surface Disinfection and Other Unnecessary Measuressupporting
confidence: 55%
“…21 , 57 59 For literature evaluating the efficiency of IRT screening for the detection of febrile international travelers, seventeen studies were identified: one aimed at detecting SARS in Canada; 60 four studies for Dengue detection in Taiwan; 12 , 13 , 61 , 62 five for Influenza in New Zealand, 63 , 64 Japan, 65 , 66 and Australia; 67 and three for Ebola virus disease (EVD) in the USA, Australia, and the UK, 68 and Sierra Leone; 69 , 70 one for MERS in Indonesia; 71 and three for COVID-19 in multiple countries. 72 74 For literature evaluating the detection of infectious diseases with measurements of vital signs, three studies were identified containing the required information for inclusion: two utilizing CMOS camera that was equipped with IRT; 75 , 76 two utilizing Doppler blood-flow meter, 10-GHz microwave radar, and thermography; 77 , 78 and one utilizing radar, finger-tip photoreflector, and thermography. 79 …”
Section: Methodsmentioning
confidence: 99%
“…Governments, airlines, airports, and other businesses serving travelers have implemented or recommended measures to reduce the risk of COVID-19 associated with air travel [15,16]. These measures have included enhanced disinfection procedures, employee health assessments, passenger health attestations, screening for fever, illness response protocols, increased spacing between passengers on flights, and other steps to reduce risk of transmission in airports and on conveyances [10,17]. Symptom-based screening at airports has proven ineffective because those measures miss mild, afebrile, asymptomatic, and pre-symptomatic SARS-CoV-2 infections [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%